Charts for an empire. A global trading zone in early modern Portuguese nautical cartography. (29th May 2019) - Sánchez, Antonio
Abstract : The global phenomenon of maritime expansion and the measures of control imposed by the interventionism of the Iberian crowns generated a context that sheds light on the Zilselian issue: the contact between artisans and university‐trained men in early modern Europe. This is an old and controversial topic. However, this article does not focus solely on the economic and social reasons for this contact, but also on epistemological and political motivations. With the specific aim of illustrating this collaboration, the article analyses some of the empirical practices developed under the Portuguese maritime empire throughout the 16th century. This is achieved through the reconstruction of the process of production of nautical charts in the Armazéns da Guiné e Índia (Storehouse of Guinea and Indies) of Lisbon, which I consider a large‐scale "trading zone." This reconstruction throws light not only on the technical complexity of these cognitive processes and the coordinated work of the different agents involved in their production, but also on the emergence of new spaces of knowledge and new communities of practitioners (with new professional statuses) linked to them; new methods of collection and management of information; and, finally, new forms of circulation and standardization of knowledge in the early modern period.